Determinants of mental health among youths and adolescents in the digital era: Roles of cyber and traditional bullying, violence, loneliness, and environment factors - Phan, Tam Chi; Chau, Brandon; Do, Ha Ngoc; Vu, Thao Bich Thi; Vu, Khanh Long; Nguyen, Hiep Duy; Nguyen, Dung Tuan; Do, Hoang Minh; Nguyen, Nga Thu Thi; La, Ly Bac Thi; Dam, Vu Anh Trong; Nguyen, Hien Thu; et al. (Frontiers in Public Health, 2022)
Introduction Although the pathogenesis of depressive disorders is not fully elucidated, untreated adolescent depression can lead to serious sequelae such as impaired academic performance and social functioning, substance use disorders, poor self-esteem, and increased risk for suicidal ideation and attempts. Literature on adolescent mental health in Vietnam is limited, despite increased international awareness of this critical issue. This study aimed to investigate the prevalence and associations of depressive symptoms in Vietnamese adolescents. Methods A cross-sectional, self-administered survey was conducted in five provinces of Vietnam among adolescents aged 14 to 24 years. In addition to collecting participants' demographics, a structured questionnaire was developed to examine depressive symptoms, suicidal ideation, loneliness, and cyberbullying victimization. Depressive symptoms and loneliness were assessed via the PHQ-9 and UCLA Loneliness Scale, respectively. Two-tailed Chi-squared, Mann-Whitney, and Kruskal-Wallis tests were performed to examine associations between variables. Multivariate Logistic regression models were conducted to examine the associations between prior-defined variables and positive depressive symptoms. Results Among 1,600 respondents, 31.8% of participants reported having mild-moderate or severe depressive symptoms. Participants within the moderate-severe depressive symptom group had significantly lower community cohesion scores than those of participants in normal and mild depressive symptom groups (p < 0.05). Youths living alone were more likely to have moderate-severe depressive symptoms (OR 2.16; 95% CI: 1.09–4.25). Cyberbullying had significant associations with depressive severity (OR 1.93; 95% CI 1.38–2.70). Conclusion The findings of this study characterize various risk and protective factors for depression in Vietnamese youths and adolescents. The results highlight the importance of raising awareness and increasing access to educational resources for depression and other mental health illnesses. With the rising prevalence of depression, parents, teachers, and community leaders play a vital role in addressing mental health problems in adolescents.